KONSEP BILANGAN RASIONAL DALAM AL-QUR’AN DAN HUBUNGANNYA DENGAN NILAI-NILAI RELIGIUS - Nasution, Sri Wahyuni (IAIN PADANGSIDIMPUAN, 2017)
Science all comes from the Qur'an, but many still doubt and even argue that science and the Qur'an are systematically integrated. Because of this problem, the writer wants to prove the relationship between the Qur'an and science is perfectly integrated by examining